Pediatric endoscopic ear surgery in clinical practice: Lessons learned and early outcomes. (30th July 2015) - Cohen, Michael S.; Landegger, Lukas D.; Kozin, Elliott D.; Lee, Daniel J.
Abstract : Objectives/Hypothesis: Only a few reports describe the outcomes following endoscopic ear surgery (EES) in children for chronic ear disease. We differentiate between transcanal endoscopic ear surgery (TEES), where the case is performed with only endoscopic visualization, from non‐TEES, where the endoscope is not used at all or used as an adjunct to the microscope. We hypothesize that EES is an effective approach to manage middle ear pathology using a transcanal approach in most cases, and can be incorporated into a pediatric otology practice with a neutral or positive effect on outcomes. Lessons learned during this process are analyzed and discussed. Study Design: Single‐institution, retrospective chart review of outcomes following TEES and non‐TEES in children from January 1, 2013 through July 1, 2014. Methods: Procedures included tympanoplasty, ossiculoplasty, and cholesteatoma resection. Primary outcome measures included closure rate of tympanic membrane perforations, audiometric outcomes, and complications. Surgical times were reported as secondary measures. Results: Ninety‐four patients underwent 121 middle ear procedures. TEES was performed in 51/121 of cases (42.1%). Comparison of TEES versus non‐TEES cases showed no significant difference in rate of tympanoplasty closure ( P > .99). The mean pure‐tone improvement following TEES tympanoplasty was −7.8 dB versus −1.33 dB for non‐TEES cases ( P = .03). Surgical times were similar between groups. Conclusions: EES techniques were readily incorporated into a pediatric otology practice. A standardized EES classification system is useful for analyzing utilization patterns and results across institutions. Tympanic membrane closure rates and hearing outcomes were similar in TEES and non‐TEES cases. Level of Evidence: 4. Laryngoscope, 126:732–738, 2016